Evolution of Rhodamine B into Near‐Infrared Dye by Phototriggered Radical Reaction and Its Application for Lysosome‐Specific Live‐Cell Imaging. Issue 9 (8th June 2016) - Lan, Haichuang; Xue, Fengfeng; Liu, Zhongkuan; Chen, Liang; Huang, Chunhui; Yi, Tao
Abstract : A facile process for preparation of near‐infrared rhodamine dye by photoirradiation is explored. When a simple rhodamine B bromoacetohydrazide is irradiated with UV light, it can evolve into a near‐infrared dye via a phototriggered radical reaction. The dye displays large spectrum shifts in preactivated and activated forms, which allows its use as a fluorescent probe in cell imaging.